Poétique de la référentialité et de la fictionalité dans la littérature viatique - Afsaneh POURMAZAHERI (Anadiss, 2018)
Who talks about the travel narrative, he also talks about the tension between the factual and the fictional. When one is interested in the study of the viatic texts, one is faced with a fictional and non-fictional dichotomous reflection. The travel narrative is torn between the desire for authenticity because it wants to be a reflection of the world and the seductions of fiction that derealise and sublimate it. Our questioning is born from the problematic of the reproduction of foreign worlds. What is played out under the process of description is not only the story told and its possible literary issues, but largely the linguistic implications of the stories. This research work is therefore concerned with theoretical issues related to gender, including those of referentiality, fictionality and subjectivity. Our main objective is to present a descriptive poetic, with the creative aspect of the language processes, of the travel narrative, whose main goal is to raise the writing procedures on the side of the authors. We also evoke the dialectic between the fictional-factual diptychs, subjectivity-referentiality and synchrony-diachrony, which are significant in the description, and which represent an important representational issue in our view, that is to say, analysis of the reflection of the Other in the text.